Existence and Perception in Medieval Vedānta - Williams, Michael (De Gruyter, 2024)
This monograph analyses metaphysics and epistemology in the medieval Mādhva tradition of Vedānta. It focuses primarily on the ideas of the sixteenth-century philosopher Vyāsatīrtha. The volume explores Vyāsatīrtha’s defence of theistic realism against the non-dualistic (Advaita) tradition of Vedānta in his masterpiece, the Nyāyāmṛta.